Pelatihan Pengajaran Bahasa Inggris Berbasis English for Specific Purposes (esp) Bagi Guru-guru Sekolah Menengah Kejuruan (SMK) Se-Kota Padang - Diah Tyahaya Iman; Lucy Suraiya; Arwina Dharma (Jurnal Pengabdian Warta Andalas, 2016)
This Community Service program is aimed at developing the state vocational shool (Sekolah Menengah Kejuruan) teachers in Padang in teaching English based on ESP (English for Specific Purposes) approach. This workshop is conducted since many SMK graduates have lack of ability in English while they should be ready-use employment in this globalized world. 20 teachers from 10 state vocational shools in Padang attended this workshop, and each school sent 2 teachers. These teachers learnt the concept of ESP related to the students’ study program, practiced on material selection and development and ESP teaching methods, performed micro-teaching, and had discussion and peer-evaluation. It is expected that SMKs will be favourite schools which produce ready-use graduates in their future workfield.